Generation Z and Doom Spending: A Predictor Analysis Hedonic Shopping Motivation and Fomo Towards Impulsive Buying in The Digital Era - Darojatu Rafiah, Azzahra; Nita Rohayati; Anggun Pertiwi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2025)
Generation Z tends to impulsively due to the influence of social media, digital advertising, and lifestyle pressures. This phenomenon is known as doom spending, which is consumptive behavior triggered by anxiety, pessimism about the future, and negative emotional impulses. Factors contributing to this behavior include hedonic shopping motivation and Fear of Missing Out (FoMO). This study aims to analyze the influence of hedonistic motivation and FoMO on impulsive purchasing. The method used is quantitative with an associative causal design. The research subjects are Generation Z (born between 1997 and 2012), comprising 204 participants selected using Cohen's formula and collected via Google Forms. The instruments used were the Impulse Buying Tendency Scale, the Hedonic Shopping Motivations Scale, and the Fear of Missing Out Scale. Data analysis was conducted using SPSS 26.0 with multiple linear regression tests. The results of the study indicate that hedonistic motivation and FoMO significantly influence impulsive purchasing, contributing 55.7%. Keywords: Doom Spending, FoMO, Generation Z, Hedonic Shopping Motivation, Impulsive Buying